2010
DOI: 10.1387/ijdb.093006jg
|View full text |Cite
|
Sign up to set email alerts
|

Expression of DOF genes identifies early stages of vascular development in Arabidopsis leaves

Abstract: The sequence of events underlying the formation of vascular networks in the leaf has long fascinated developmental biologists. In Arabidopsis leaves, vascular-precursor procambial cells derive from the elongation of morphologically inconspicuous ground cells that selectively activate expression of the HD-ZIP III gene ATHB8. Inception of ATHB8 expression operationally defines acquisition of a typically irreversible preprocambial cell state that preludes to vein formation. A view of the constellation of genes wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(59 citation statements)
references
References 57 publications
1
56
0
2
Order By: Relevance
“…By contrast, expression levels of MONOPTEROS (MP), TDR, ARABIDOPSIS THALIANA HOMEOBOX 8 (AtHB8), and TARGET OF MP 6 (TMO6), which are well-known marker genes for preprocambial and procambial cells (Hardtke and Berleth, 1998;Hirakawa et al, 2008;Donner et al, 2009;Schlereth et al, 2010), were significantly increased at 12 and 24 hai ( Figure 4A). Consistently, most other genes that had been reported to be expressed in leaf procambial cells (Clay, 2002;Ohashi-Ito and Fukuda, 2003;Nagawa et al, 2006;Scarpella et al, 2006;Konishi and Yanagisawa, 2007;Kwaaitaal and de Vries, 2007;Gardiner et al, 2010;Hou et al, 2010;Gardiner et al, 2011;Lin et al, 2012;Peret et al, 2012) were up-regulated at 24 hai ( Figure 4C). At 36 hai, expression levels of xylem-specific genes such as VND6, XYLEM CYSTEINE PROTEASE 1 (XCP1), and LOB DOMAIN-CONTAINING PRO-TEIN 15 (LBD15) (Zhao et al, 2000;Kubo et al, 2005;Yamaguchi et al, 2011) were enormously higher ( Figure 4B).…”
Section: Expression Of Vascular-related Genes In Leaf-disk Culturesupporting
confidence: 81%
“…By contrast, expression levels of MONOPTEROS (MP), TDR, ARABIDOPSIS THALIANA HOMEOBOX 8 (AtHB8), and TARGET OF MP 6 (TMO6), which are well-known marker genes for preprocambial and procambial cells (Hardtke and Berleth, 1998;Hirakawa et al, 2008;Donner et al, 2009;Schlereth et al, 2010), were significantly increased at 12 and 24 hai ( Figure 4A). Consistently, most other genes that had been reported to be expressed in leaf procambial cells (Clay, 2002;Ohashi-Ito and Fukuda, 2003;Nagawa et al, 2006;Scarpella et al, 2006;Konishi and Yanagisawa, 2007;Kwaaitaal and de Vries, 2007;Gardiner et al, 2010;Hou et al, 2010;Gardiner et al, 2011;Lin et al, 2012;Peret et al, 2012) were up-regulated at 24 hai ( Figure 4C). At 36 hai, expression levels of xylem-specific genes such as VND6, XYLEM CYSTEINE PROTEASE 1 (XCP1), and LOB DOMAIN-CONTAINING PRO-TEIN 15 (LBD15) (Zhao et al, 2000;Kubo et al, 2005;Yamaguchi et al, 2011) were enormously higher ( Figure 4B).…”
Section: Expression Of Vascular-related Genes In Leaf-disk Culturesupporting
confidence: 81%
“…Behavior of SHR expression in leaves developing under conditions of reduced auxin transport, which dramatically changes the architecture of ATHB8 expression domains and of vein networks (Mattsson et al, 1999;Sieburth, 1999;Gardiner et al, 2010), was comparable to that observed under undisturbed vein patterning. All aspects of SHR expression, including relation to ATHB8 expression and association with positions of vein formation, proved to be highly reproducible under all experimental conditions.…”
Section: Transition To Preprocambial Cell Statementioning
confidence: 72%
“…All the genes whose expression has previously been assigned to early stages of leaf vein development have also been reported to be expressed in the root procambium (e.g., Baima et al, 1995;Hardtke and Berleth, 1998;Steinmann et al, 1999;Kang and Dengler, 2004;Scarpella et al, 2004Scarpella et al, , 2006Alonso-Peral et al, 2006;Konishi and Yanagisawa, 2007;Wenzel et al, 2007;Carland and Nelson, 2009;Gardiner et al, 2010), and identification of leaf vascular gene expression profiles based on root procambial expression has proved to be an effective strategy (Gardiner et al, 2010). Reporter gene expression in the J2501 and Q0990::mGFP5er enhancer-trap lines and in transcriptional fusions to SHR or to WOODENLEG/CYTO-KININ RESPONSE1/ARABIDOPSIS HISTIDINE KINASE4 (Mahonen et al, 2000;Inoue et al, 2001;Suzuki et al, 2001; WOL hereafter) has consistently been used as reliable marker of root procambial cells (e.g., Benkova et al, 2003;Birnbaum et al, 2003;Wang et al, 2005;Zhang et al, 2005;Dello Ioio et al, 2007;Hirota et al, 2007;Mustroph et al, 2009;Petersson et al, 2009; Fig.…”
Section: Leaf Expression Of Root Vascular Markersmentioning
confidence: 99%
“…Dof TFs also play important roles in the regulation of secondary metabolic processes, such as biosynthesis of glucosinolates and flavonoids (Skirycz et al, 2006(Skirycz et al, , 2007, and cell cycle regulation (Skirycz et al, 2008). Dof TFs were also reported to be associated with various physiological processes, such as the formation of inter-fascicular cambium and vascular development (Konishi and Yanagisawa, 2007;Guo et al, 2009;Gardiner et al, 2010), regulation of leaf axial patterning (Kim et al, 2010), flower abscission (Wei et al, 2010), guard cell differentiation (Negi et al, 2013), photoperiodic flowering (Fornara et al, 2009), circadian clock (Iwamoto et al, 2009;Yang et al, 2011), plant hormonal signaling (Yanagisawa, 2002(Yanagisawa, , 2004Moreno-Risueno et al, 2007b), and biotic and abiotic stress tolerance of plants (Corrales et al, 2014;Ma et al, 2015;Sasaki et al, 2015).…”
Section: Introductionmentioning
confidence: 99%